Pursuing the Long Shadow over the "Domestic Church": Toward a Global History of Abuse in Catholic Settings - Faggioli, Massimo (The catholic historical review, 2024)
This article makes the case for a new phase of research on the abuse crisis and calls for a collaborative endeavor aiming at an interdisciplinary, historically contextualized account of the global history of abuse of children and vulnerable adults in the Catholic Church. This requires a redefinition of the scope of enquiry from the national to the global, and a refocusing of the analytical optic beyond a perpetrator-focused, pathologizing approach to clergy sexual abuse to situate sexual and spiritual abuse in the Catholic Church in its wider enabling ecosystem. We propose a scaled and spatial approach, focused on delineating understandings of the "domestic church" in a given context. This broader focus on interactions between the "three-legged stool" of the family-parish-school, particularly as contextualized in their ecclesial and socio-economic dynamics, extends the analysis beyond media-framed narratives and judicial approaches and allows for comparability across national settings. The article sets out the urgent need for a multi-disciplinary, mixed-method, and coordinated approach, given the many facets of the crisis (legal, political, cultural, financial, psychological, but also theological and spiritual), and the transnational dimensions of this epidemic within (and beyond) the Church that are yet to be fully discerned and historicized.